Effect of the reaction medium on the immobilization of nutrients in hydrochars obtained using sugarcane industry residues - Silva, Camila Centurion [UNESP]; Melo, Camila Almeida [UNESP]; Soares Junior, Francisco Holanda; Moreira, Altair Benedito [UNESP]; Ferreira, Odair Pastor; Bisinoti, Márcia Cristina [UNESP] (Elsevier, 2017)
In this study, nutrients were immobilized on the hydrochars obtained by hydrothermal carbonization (HTC) of a vinasse and sugarcane bagasse mixture, in the presence of acid, base and salt additives at temperatures of 150, 190 and 230 °C. The increase in temperature caused higher immobilization of Ca, Mg, K, N, Cu, Mn, Zn, B, P and Fe in all hydrochars produced. H3PO4 and NaOH immobilized higher amounts of P, Mg and Mn, while Ca was immobilized in higher quantities in the presence of H3PO4 and (NH4)2SO4. The addition of H2SO4, H3PO4 and (NH4)2SO4 was responsible for an increased immobilization of P, N, Ca, Mg and K. The immobilization of B, not present in the starting raw material, was possible with the addition of H3BO3. The results showed that it is possible to alter the reaction medium to immobilize nutrients on hydrochars produced from vinasse and sugarcane bagasse, for agricultural applications.
Keywords: Hydrothermal carbonization; Immobilization; Sugarcane bagasse; Vinasse